Intellectual Leadership in the Knowledge Economy: Nurturing Innovation and Learning Organizations - Suktam, Asst. Prof. Dr.Wanchai; Supsin, Jirayu; Kenpahoom, Sanya (The Journal of International Buddhist Studies College, 2024)
In the knowledge economy, intellectual leadership plays a critical role in directing organizations through the promotion of inquisitiveness, creativity, and ongoing education. This makes it possible for businesses to take advantage of intellectual capital, which spurs growth, innovation, and long-term success. Skillfully navigating the intricacies of the knowledge economy, intellectual leadership fosters innovation by promoting knowledge sharing, lifelong learning, and ethical principles. It is essential to assess its efficacy and acknowledge the contribution of intellectual agility to innovation. Innovation and intellectual capital act as mediators between the positive effects of transformational and transactional leadership on organizational performance. Case studies of intellectual leaders from the real world provide insightful information about how successful leadership fosters innovation.